2000
DOI: 10.1093/ps/79.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorolytic and cell wall-degrading enzymes on the performance of growing broilers fed wheat-based diets containing different calcium levels

Abstract: A study was conducted to determine the cumulative effects of phosphorolytic enzymes, cell wall-degrading enzymes, and citric acid and Ca levels on feed intake, BW gain (BWG), feed conversion, intestinal viscosity, and toe ash of broilers (d 1 to 21) fed wheat-based diets. Broilers were fed the following six diets at either 0.59, 0.69, or 0.79% Ca: 1) a negative control (NC) diet, 0.17% available P; 2) NC + 750 phytase units/kg diet; (3) phytase + 3,156 units of acid phosphatase/kg diet; 4) phytase + acid phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Scott et al (1998b) reported that the wheat cultivar that was used in this trial was improved considerably by the addition of xylanase, indicating that a high level of xylans may have been present. Recently similar interactions between enzymes were reported for broilers fed wheat (Zyla et al 2000).…”
Section: Discussionsupporting
confidence: 75%
“…Scott et al (1998b) reported that the wheat cultivar that was used in this trial was improved considerably by the addition of xylanase, indicating that a high level of xylans may have been present. Recently similar interactions between enzymes were reported for broilers fed wheat (Zyla et al 2000).…”
Section: Discussionsupporting
confidence: 75%
“…These results were obtained for maize-soybeans based diets. Zyla et al (2000) showed that phytase addition to wheat-soya based diets had no significant effect on bone mineralization. This different observation can be explained by Underwood's finding (1981) that the Ca to nonphytate phosphorus ratio beyond 2 : 1 reduces bioavailability of Ca and P due to the formation of insoluble calcium-phosphate complex in the chicken gut.…”
Section: Discussionmentioning
confidence: 99%
“…Zyla et al (2000) showed that supplementation of 750 PU/kg to wheat based diet increased body weight gain, feed consumption and phosphorus retention. Supplementation of phytase (1 200 PU/kg) improved the digestibility of protein and amino acids in maize, sorghum and wheat based diets, but the magnitude of response varied between cereals (Ravindran et al, 1999).…”
mentioning
confidence: 99%
“…The magnitude of response varied between cereals. Supplemental phytase improved phosphorus retention in broilers fed wheat (Leske and Coon, 1999;Zyla et al, 2000), wheat midds, barley, defatted rice bran and canola based diets (Leske and Coon, 1999).…”
mentioning
confidence: 99%